2004
DOI: 10.1021/cm035107a
|View full text |Cite
|
Sign up to set email alerts
|

Cracking and Orientation of Solution-Deposited Rutile TiO2 Films

Abstract: In this study, c-axis oriented rutile phase TiO2 films were deposited at 60 °C on silica glass substrates from acidic TiCl4 aqueous solutions. X-ray diffraction and scanning electron microscopy showed that oriented film growth was the result of a combination of preferential growth of the primary crystallites and a geometrical constraint imposed on agglomerating crystallites. It was also observed that the film cracked during drying. The severity of cracking was reduced when the wash solvent was changed from wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 12 publications
2
38
0
Order By: Relevance
“…Strontium titanate has a dielectric constant of 330 [26]. Although these ceramic materials have high dielectric constants, they suffer from being brittle materials that are rather inflexible, prone to cracking, and difficult to incorporate into printing methods [32].…”
Section: Nanostructured Dielectricsmentioning
confidence: 99%
“…Strontium titanate has a dielectric constant of 330 [26]. Although these ceramic materials have high dielectric constants, they suffer from being brittle materials that are rather inflexible, prone to cracking, and difficult to incorporate into printing methods [32].…”
Section: Nanostructured Dielectricsmentioning
confidence: 99%
“…The 'mud crack' type pattern observed indicates that the film cracked as a result of a biaxial tensile stress [16]. Since biaxial tensile stresses can be generated during film growth, when the film is cooling to room temperature after growth and when the film is drying, determining the point at which the film cracked gives an idea of the strain mechanisms in- Observations with an optical microscope indicated that the crack openings for the 24 h film (see Fig.…”
Section: Film Growth and Crackingmentioning
confidence: 97%
“…Films with columnar structures tend to be porous as pores can be formed at the junctions of neighboring crystallites [12]. Therefore, the 200 • C film could likely be more porous than the 50 • C film.…”
Section: Structurementioning
confidence: 99%